Mengurai Nama Diri: Alternatif Ekspresi Tulis Puisi - Edy Suprayetno (EUNOIA (Jurnal Pendidikan Bahasa Indonesia), 2021)
Concerning the expression of poetry writing is any activity that allows us to get an artistic experience in writing poetry. By the time you find extraordinary event, for example, saw the fall of the aircraft, a total solar eclipse, the dark during the day due to the eruption of a volcano, got a prize draw hundreds of millions of dollars, or meet with relatives who had disappeared a few years, what feelings would overflow ? Sad, happy, happy, or a mixture of them all? The experience is a valuable ingredient when expressed through poetry. Humans are able to greet each mengela and because it has a name. Concern for the proper name can be used to learn to write poetry. The trick, is to line up our name vertically. Then, develop your imagination and creativity to continue any initials or the initial letter. Having regard to the techniques of writing poetry following: (1) Polisindeton, (2) Impression, (3) Alusi, (4) Dramatic, (5) Anadiplosis, (6) paradox, (7) Analogies (philosophy), (8) Comparing direct an episode (actual) with past events (publicly known), (9) Alliteration and (10) assonance.